(3SdhGf GdeWGY aj YOhGf GdCJHGYs - (3eMeO Hf CHj GdbGSe Hf Ydj GdbQTj Gdecj MLI GdOjf GdfMhj, GHf GdeXaQ,J (B568 (3g` s
(3ChdgG (B:s
(3hHYO aEf eeG CaVi Hg Edjg EVWQGQ GdEZJQGH hCJjGH GdEcJFGH Cf CXaQ aj Gddg JYGdi hdg GdMeO HehGNGJ ebjd YKQGJ GdSGOGI s
(3BNQgG (B:s
(3hCSJcajg Yhd GdSDGd ceG CSJYajg ef YhGd GdLhGH hGSJOaY Hg aSGO GdNWGA ceG CSJOaY Hg cSGO GdUhGH Je cJGH SdhGf GdeWGY aj YOhGf GdCJHGY s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B998s
Keywords: (3GdJUha hGdBOGH GdTQYjIs